Implementation of PBL and IBL Models Assisted by Video Media to Improve Critical Thinking Skills - Munawir Yusuf; Subagya; Iwan Maulana; Mochamad Kamil Budiarto (Jurnal Ilmiah Sekolah Dasar, 2022)
Teaching social science in elementary schools is not only conveying theories but also real forms of implementation and problems that often arise in the daily environment. This is be able to develop students' critical thinking in reconstructing events and the values contained therein. However, the media and learning methods used today have not been able to improve students' critical thinking skills. This study aims to analyse the improvement students' critical thinking skills through the application of collaboration between PBL and IBL models using video. The research subjects were elementary school students who were in grade 5, consisting of 30 students. The instrument used for data collection in this study was a descriptive description test. The data analysis technique used in this research is descriptive statistical technique. This research design uses classroom action research which consists of three cycles. The results showed that critical thinking skills increased in each cycle. In the first cycle, 50.33% of critical thinking skills in the second cycle increased to 69.83% and in the third cycle increased to 78.38%. So the conclusion from the results of this study is that the implementation of PBL and IBL models through video media is proven to be able to improve students' critical thinking skills, thus, it is proven that the integration between innovative learning models and learning media contributes positively to the improvement of students' abilities and competencies.